Pengembangan Media Pembelajaran Berbasis Video Animasi dengan Model Pembelajaran Inkuiri Terbimbing untuk Meningkatkan Motivasi dan Hasil Belajar Peserta Didik - Sya’bania, Nursina; Anwar, Muhammad; Wijaya, Muhammad (Chemistry Education Review (CER), 2020)
This research is a study development that aims to develop an animated video-based learning media with guided inquiry learning models to increase students’ motivation and learning outcomes on chemical equilibrium materials that are valid, practical, and effective. The development model used in this study refers to the 4D development model, which consists of the defining stage, the design stage, the development stage, and the dissemination stage. The results of this study indicate that 1) the assessment of media validity by the media and material experts is in very valid category, 2) the responses of students and teachers to the learning media developed also received very high categories so that the media is stated as  practical, 3) The learning motivation of the class that uses animation media (MA) is also higher than the class that doesn’t use animation media (TMA) with a value of 81.33 and 71.41. In the field test phase to 33 students of the class MA and 32 of the class TMA students of SMAN 11 Makassar obtained class completeness by 84.8% and 75% respectively. Based on Mann Whitney-U test obtained the significance of the p value is smaller than α (0.014 < 0.05), which means there are differences between the two groups significantly. The animated video-based learning media that had been developed with 4D model is valid, practical, and effective to be applied in learning.